The music of a Lunda Kalendi - Davidson, Marjory (International Library of African Music, 1964)
In the last issue of the Journal I gave some details of an eight-keyed Lunda Kalendi with the tuning and the harmonic framework of the music. Since then I have been able to write down the variations. I am greatly indebted to Mr. Noah Kambidima, the owner of this kalendi who has not only spent a great deal of time helping me to write down his music but also lent me his instrument to practise upon so that I could learn to play the music myself.
Keywords: Music; Southern Lunda (African people); Mbira; Ethnomusicology; Mbira music; Musical instruments; Instrument Construction; Lunda Kalendi (Instrument); Zambia; African Music; Mbira (Instrument)